Effect of physical endurance on the course of fight and level of sports performance in cadet judokas - Lech, G.; Palka, T.; Sterkowicz, S.; Tyka, A.; Krawczyk, R. (Archives of Budo, 2010)
Background and study aim: The goal of the present study was to provide answer to the following question: Is physical capacity in judo contestants at cadet age related to the adopted fighting strategy and the level of sports achievement? Material and methods: The study covered eight judo contestants from four clubs throughout Poland. First stage involved registration of their competitive activity level. Based on this record, contestants` fighting activity, effectiveness and level of performance were assessed. Another stage of the investigations focused on evaluation of their aerobic and anaerobic capacity measured by means of testing methods used within Instytut Fizjologii Czlowieka AWF (the Institute for Human Physiology in the University School of Physical Education in Krakow). The strength of the relationship was concluded based on the value of Spearman`s rank correlation coefficient (Rs). Results: Statistical analysis revealed that the level of anaerobic capacity at the cadet age shows a relationship with the method of fighting. Particularly important indexes here are: total work (TW) and peak power output (expressed in relative values, RPP). TW values were positively correlated with activity and effectiveness of actions during first part of fight whereas RPP was connected with activity in first part of match and high effectiveness during the whole match. No statistically significant correlations were observed between the level of achievement and the value of physical capacity. Conclusions: 1. Level of anaerobic capacity plays a specific role in the course of fight among judo cadets. 2. Individual functional abilities in judo contestants should be taken into consideration during the process of technical and tactical coaching.